Oxidation Electrode for Electrochromic Energy Storage Device and Transparent Large-Area Smart Window with Electrochromic and Energy Storage Functions Including the Same

KR103020342B1Active Publication Date: 2026-09-15PUSAN NAT UNIV IND UNIV COOPERATION FOUND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250036735
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2026-09-15
Estimated Expiration
2045-03-21

Smart Images

  • Figure 112025032536820-PAT00002_ABST
    Figure 112025032536820-PAT00002_ABST
Patent Text Reader

Abstract

The present invention provides a polyviologen | zinc mesh | WO3·2H2O-based electrochromic energy storage device (EESD) and implements four electrochromic modes capable of independently controlling visible light and near-infrared (NIR) transmittance. Furthermore, it provides excellent electrochromic performance and enhanced energy storage efficiency through the formation of a uniform electric field and a fast response speed utilizing a solid electrolyte. By applying a PEDOT:PSS protective layer, the stability of the polyviologen is increased, and self-coloring and self-bleaching functions are implemented, enabling operation without separate energy consumption. Through this, the smart window of the present invention enables high-efficiency energy storage and indoor light and heat control, thereby reducing energy consumption in buildings and contributing to the realization of a net-zero energy system.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to electrochromic and energy storage technology, and more specifically, to an oxide electrode used in an electrochromic energy storage device (EESD) and a transparent large-area smart window including the same. The present invention relates to a technology that simultaneously provides an electrochromic function capable of controlling visible light and near-infrared transmittance and an energy storage function capable of storing and releasing energy. The present invention can provide an innovative solution for energy saving and smart optical control in various application fields such as buildings, automobiles, displays, and wearable electronic devices. Background Technology

[0002] Building energy accounts for more than 30% of total energy consumption and 10% of greenhouse gas emissions, with heating, ventilation, and air conditioning (HVAC) systems being one of the major factors consuming the most energy. With the recent widespread use of glass curtain walls in buildings, HVAC energy consumption is increasing due to the structural limitations of conventional windows, which allow heat and light to pass through freely. Consequently, electrochromic (EC) smart windows are attracting attention as a technology to improve building energy efficiency and reduce heating and cooling loads.

[0003] An ideal smart window should be able to actively manage the influx of indoor light and heat by adjusting transmittance in the visible (380-780 nm) and near-infrared (780-2520 nm) regions according to voltage. However, existing electrochromic smart windows have been limited to providing simple color changes, and technology to implement energy storage functions utilizing this has not yet been sufficiently developed.

[0004] Recently, zinc-based aqueous electrochromic energy storage devices (EESDs) have been attracting attention due to their low cost, high performance, safety, and energy saving effects. Through these devices, a concept has been proposed in which smart windows can store and recycle energy by integrating electrochromic and energy storage functions.

[0005] In conventional EESD designs, it was common practice to place a zinc thin film as the central electrode; however, this method has limitations as the opaque zinc thin film reduces transparency, making it difficult to apply to large-area smart windows. Additionally, the placement of the central electrode limits the contact area with the electrolyte, and since it is difficult to apply in a solid state, it is mostly limited to small-area and liquid-based devices.

[0006] Viologen, which has been widely studied as an electrochromic cathode material, possesses advantages such as high reversibility, long lifespan, environmental safety, and low cost, and is utilized as a core material in existing electrochromic devices (ECDs). However, research on viologen-based EESDs is still lacking, and there are several technical issues that need to be resolved for commercialization.

[0007] The first problem is the low electrical conductivity of viologen. Since viologen is an organic material with inherently low electrical conductivity, it is utilized within an ion gel in conventional ECDs and designed to improve reaction rates by coming into direct contact with the anode material. However, this design approach can significantly degrade energy storage performance and is difficult to apply to existing EESDs.

[0008] To overcome this, some studies have introduced designs in which viologen is mixed with carbon or polymer materials to be used as an electrode, or fabricated into a separate film form to insulate a zinc anode with an electrolyte. However, these methods have resulted in problems such as degraded electrochromic performance, reduced transparency, poor uniformity of color change, and significantly slower response speeds. Furthermore, even when polymer structures are introduced, practical application remains difficult due to low transparency, low conductivity, and unresolved stability issues such as expansion and corrosion.

[0009] Consequently, to commercialize viologen-based EESD technology, a new design is required that enables large-area implementation while maintaining a balance between electrochromic performance and energy storage performance. Through this, it is necessary to overcome existing limitations and maximize the building energy saving effect using smart windows. The problem to be solved

[0010] Conventional electrochromic smart windows have limitations, such as insufficient energy storage capabilities, slow response speeds, and difficulty in implementing them on a large scale. In particular, existing zinc-based EESDs use opaque zinc thin films, resulting in low transparency and limited contact with the electrolyte, while viologen-based devices suffer from slow color conversion speeds and difficulty in achieving uniform color change due to low conductivity.

[0011] The present invention proposes a transparent viologen-based EESD, characterized by implementing four electrochromic modes through a dual cathode structure and achieving a visible-near-infrared dual-band EC energy storage function. To this end, polyviologen and WO3·2H2O are applied as cathode materials, and PEDOT:PSS is used as a protective layer and a proton supply layer to increase conductivity and prevent the decomposition of viologen.

[0012] In addition, a transparent zinc mesh coated with a UV-cured solid electrolyte is applied to form a uniform electric field and maintain high transparency. As a result, the EESD of the present invention provides high transparency, fast switching speed, excellent color change uniformity, and superior energy storage performance, and enables large-area implementation.

[0013] The present invention aims to reduce building energy consumption and optimize indoor light and heat control through a smart window that simultaneously provides electrochromic and energy storage performance. means of solving the problem

[0014] In one aspect, the present invention provides an oxidation electrode used in an electrochromic energy storage device, comprising: a metal mesh electrode; and a curable solid electrolyte layer formed on the surface of the mesh electrode.

[0015] Conventional electrochromic devices either perform only the electrochromic function or suffer from poor durability due to the use of liquid electrolytes. In particular, the use of opaque electrodes made it difficult to apply to large-area smart windows and to simultaneously implement energy storage functions. Additionally, there were limitations in applying reduction electrodes via solution processes. This invention aims to resolve the problems of existing technologies by providing a transparent oxidation electrode utilizing a solid electrolyte, thereby enabling the simultaneous implementation of electrochromic and energy storage functions.

[0016] The oxidation electrode according to the present invention is designed to simultaneously perform electrochromism and energy storage by including a metal mesh electrode and a UV-cured solid electrolyte layer. This provides the following effects.

[0018] The above solid electrolyte is manufactured by preparing a polymer solution by dissolving an acrylic monomer, a monomer containing an anionic functional group, a crosslinking agent, a metal salt, and a UV initiator in deionized water, applying the prepared polymer solution to the mesh electrode layer, and then curing it by irradiating it with UV light.

[0019] The above acrylic monomer may be acrylamide (AAm), methacrylamide (MAAm), hydroxyethyl acrylamide (HEAAm), or a combination thereof.

[0020] The monomer containing the above anionic functional group may be 2-acrylamido-2-methylpropanesulfonic acid (AMPS), sodium 4-styrenesulfonic acid (SSS), acrylic acid (AA), methacrylic acid (MAA), or a combination thereof.

[0021] The above crosslinking agent may be N,N'-methylenebisacrylamide (MBAA), polyethylene glycol diacrylate (PEGDA), divinylbenzene (DVB), or a combination thereof.

[0022] The metal salt may be zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc nitrate (Zn(NO3)2), magnesium chloride (MgCl2), calcium chloride (CaCl2), or a combination thereof.

[0023] The above UV initiator may be 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, Irgacure 2959, Irgacure 184, Darocur 1173, or a combination thereof.

[0024] The solid electrolyte of the present invention is formed by dissolving a composition comprising an acrylic monomer, a monomer containing an anionic functional group, a crosslinking agent, a metal salt, and a UV initiator in deionized water, applying it to a mesh electrode layer, and curing it by irradiating it with UV light. In this process, a polymer network is formed, and a solid electrolyte layer with excellent electrical conductivity and ion mobility is formed by the bonding of the compositional components. The solid electrolyte comprises a copolymer of an acrylic monomer (AAm, MAAm, HEAAm) and a monomer containing an anionic functional group (AMPS, SSS, AA, MAA), thereby allowing for the control of hydration and ion conductivity. Furthermore, due to the presence of a crosslinking agent (MBAA, PEGDA, DVB), it has a 3D network structure with methylene crosslinks (-CH2-) formed rather than a simple polymer network, thereby improving mechanical strength and durability. Metal salts (ZnCl2, ZnSO4, Zn(NO3)2, MgCl2, CaCl2) serve as ion sources for electrochromic and energy storage devices, and in particular Zn 2+The composition containing [the component] enables a charge-discharge mechanism through interaction with the zinc mesh electrode. The UV initiator (2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, Irgacure 2959, Irgacure 184, Darocur 1173) induces radical polymerization upon UV irradiation, allowing the solid electrolyte to cure rapidly and contributing to the formation of a uniform network. By applying the solid electrolyte of the present invention, problems such as leakage, evaporation, and mechanical instability that occurred in conventional liquid electrolyte-based electrochromic devices can be resolved. Furthermore, by being formed directly on the mesh electrode layer, electrochemical stability is improved, and high ion mobility is maintained even in the solid state, enabling stable long-term performance of electrochromic and energy storage functions. As such, the present solid electrolyte improves the stability and performance of electrochromic devices, and is suitable for large-area smart window applications due to the simpler manufacturing process compared to conventional electrolyte-based systems.

[0026] The above solid electrolyte layer has a polymer main chain containing an acrylic monomer and a polymer side chain containing an anionic functional group, forms a cross-linked polymer network cross-linked by methylene (-CH2-) cross-linking, and cations are dispersed within the cross-linked solid electrolyte.

[0027] The above acrylic monomer may be acrylamide (AAm), methacrylamide (MAAm), hydroxyethyl acrylamide (HEAAm), or a combination thereof.

[0028] The above anion may be a sulfate ion.

[0029] The above cation may be zinc, magnesium, calcium, or a combination thereof.

[0030] The solid electrolyte of the present invention comprises a polymer main chain containing an acrylic monomer and a polymer side chain containing anionic functional groups, and is characterized by a cross-linked polymer network formed through methylene (-CH2-) cross-linking. Through this structure, mechanical stability and ion mobility are simultaneously secured, and long-term stability of electrochromic and energy storage devices can be guaranteed. The main chain of the solid electrolyte consists of acrylamide (AAm), methacrylamide (MAAm), and hydroxyethyl acrylamide (HEAAm), which play an important role in controlling hydration and securing mechanical strength. In particular, AAm and MAAm form strong hydrogen bonds to improve the structural stability of the polymer, while HEAAm imparts hydrophilicity to increase ion mobility within the electrolyte. Additionally, sulfate ions (SO₄) contained in the side chain 2- ) is a cation (Zn 2+ , Mg 2+ , Ca 2+ It promotes ion migration through electrostatic interactions with ) and stabilizes cations within the electrolyte, enabling rapid and uniform charging and discharging. By forming a 3D network structure through methylene cross-linking, this solid electrolyte enhances mechanical strength and maintains high durability compared to liquid electrolytes. Zn within this polymer network 2+ , Mg 2+ , Ca 2+ Effective interaction with the electrode is possible through the dispersion of cations, thereby maximizing charge and discharge performance. Actual experimental results confirmed that when this solid electrolyte is applied, the discharge capacity increased by more than double (141.9 mAh / m²) compared to the existing (73.2 mAh / m²), significantly improving energy storage performance.

[0032] In another aspect, the present invention provides a smart window having transparent large-area electrochromic and energy storage functions.

[0033] As an example, a smart window may have a single reduction electrode structure. The smart window comprises: the oxidation electrode described above; a first reduction electrode portion located on one side of the oxidation electrode; and a first power supply unit connecting the oxidation electrode and the first reduction electrode portion, wherein the first reduction electrode portion comprises: a first electrochromic layer laminated on one side of the oxidation electrode; and a first transparent electrode laminated on the first electrochromic layer.

[0034] As another example, a smart window may have a reduction electrode structure. The smart window comprises a second reduction electrode located on the other side of the oxidation electrode; and a second power supply connecting the oxidation electrode and the second reduction electrode. The second reduction electrode comprises a second electrochromic layer laminated on the other side of the oxidation electrode; and a second transparent electrode laminated on the second electrochromic layer. The transmission and blocking wavelength bands of the first electrochromic layer and the second electrochromic layer are different from each other.

[0035] The first electrochromic layer comprises polyviologen and further comprises a PEDOT:PSS conductive polymer layer between the oxidation electrode and the first electrochromic layer.

[0036] The PEDOT:PSS layer used in the present invention serves as both a protective layer and a proton-providing layer, and is a key element in improving the performance of electrochromic and energy storage devices. First, as a protective layer, PEDOT:PSS prevents direct contact between the polyviologen (PV), the electrolyte, and the electrode, thereby suppressing the degradation of the PV and enabling an extended lifespan. Generally, while PV possesses high electrochemical activity, there is a possibility of degradation due to moisture and zinc ions in the electrolyte during long-term use. In the structure of the present invention, the PEDOT:PSS layer protects the PV to prevent moisture absorption and ion erosion, and provides long-term electrochemical stability.

[0037] Furthermore, PEDOT:PSS acts as a proton-providing layer to increase the electrochromic reaction rate. PEDOT is a conductive polymer capable of simultaneously transporting cations (H+) and electrons; by promoting the oxidation-reduction reaction of polyviologen, it enables faster color change and decolorization response speeds. Experimental results show that when the PEDOT:PSS layer is included, the color change response speed increases by more than 10 times compared to the conventional method, and the decolorization and coloring times are reduced to 0.8 seconds and 1.8 seconds, respectively. Additionally, compared to the case without PEDOT:PSS, the discharge capacity of the electrochromic device is 73.2 mAh m⁻¹. -2 At 141.9 mAh m -2As it increases, energy storage performance is significantly improved. In addition, PEDOT:PSS also plays a role in reducing interfacial resistance with the electrode. In the present invention, when a PEDOT:PSS layer is included, the contact resistance between electrodes decreased from 1356.7 Ω to 532.3 Ω, which facilitates electron movement and acts as a factor in improving the electrochemical performance of the device.

[0039] The first electrochromic layer comprises polyviologen and further comprises a PEDOT:PSS conductive polymer layer between the oxidation electrode and the first electrochromic layer, and the second electrochromic layer comprises WO3·H2O or WO3.

[0040] The present invention is designed to simultaneously perform electrochromic and energy storage functions in a transparent, large-area smart window, and can implement four electrochromic modes to control light transmittance in various environments. The smart window of the present invention includes dual electrochromic layers, and each electrochromic layer operates in different wavelength bands to independently control the transmission and blocking of visible light and near-infrared (NIR). Through this, functions such as indoor lighting control, energy saving, and privacy protection can be efficiently performed.

[0041] When the smart window operates in Transparent Mode, both visible light and near-infrared light are transmitted in the default state where no voltage is applied, and the window remains completely transparent. This mode allows maximum natural light to enter the room, providing a bright and open environment, and has the advantage of maximizing lighting without consuming power.

[0042] In Visible Colored Mode, the polyviologen (PV)-based electrochromic layer is activated, allowing it to selectively absorb or reflect visible light. At the same time, near-infrared light is transmitted, enabling the control of indoor brightness while minimizing thermal effects. Therefore, it can be usefully applied in environments requiring privacy protection and glare prevention, and is effective in applications where external visibility must be blocked without affecting indoor temperature control.

[0043] In NIR Colored Mode, the WO3·H2O-based electrochromic layer is activated, blocking near-infrared (NIR) radiation. In this state, thermal energy can be blocked while maintaining sunlight's visible light, making it effective for stably regulating indoor temperatures. In particular, it maximizes energy savings to reduce cooling loads during the summer and is suitable for environments where natural light can be utilized, as visible light is preserved.

[0044] In Fully Colored Mode, the polyviologen and WO₃·H₂O-based electrochromic layers are simultaneously activated, blocking both visible and near-infrared light. In this state, light ingress is minimized, making it possible to maintain a constant indoor temperature. By completely blocking the influence of external light, it can provide privacy protection and be utilized in extreme weather conditions or environments with strong sunlight.

[0045] The smart window of the present invention can selectively implement these four modes through voltage regulation, thereby providing optimal light control and energy efficiency in various environments requiring solar control, such as building and vehicle windows, wearable displays, and solar energy control. Unlike conventional simple electrochromic technology, the smart window of the present invention can maximize the usability of electrochromic elements and increase energy saving effects through a structure that can independently control visible light and near-infrared light. Effects of the invention

[0047] The present invention enables the optimization of indoor light and heat control and the reduction of building energy consumption by implementing a smart window that simultaneously provides electrochromic and energy storage functions. In particular, by applying a dual cathode structure (polyviologen + WO₃·2H₂O) to implement four electrochromic modes, the transmittance of visible light and near-infrared light can be controlled independently. Furthermore, by adopting a transparent zinc mesh electrode coated with a UV-cured solid electrolyte, a uniform electric field is formed while maintaining high transparency, thereby providing a faster color change speed, excellent color conversion uniformity, and enhanced energy storage performance compared to existing technologies. Brief explanation of the drawing

[0048] Figure 1 shows the structure and operating principle of a polyviologen | zinc mesh (Zn mesh) | WO₃·2H₂O electrochromic device. (a) shows the structure and operating principle of the device for controlling visible light and near-infrared (NIR) in a winter environment, and (b) shows the structure and operating principle of the device for controlling visible light and near-infrared (NIR) in a summer colored state. Figure 2 shows a comparative analysis of electrochemical characteristics. (a) schematically illustrates the structure and operating principle of a polyviologen | zinc mesh (Zn mesh)-based EESD. (b) is an SEM image showing the zinc mesh surface and a cross- section of the device. (c) shows the chemical structure and redox mechanism of polyviologen. (d) compares the cyclic voltammetry (CV) curves of the polyviologen | zinc mesh EESD with and without a PEDOT:PSS layer at various scan rates. (e) shows a scan rate of 2 mV s⁻¹. -1 (f) shows a comparison of CV curves with and without PEDOT:PSS. (f) shows the linear relationship between the anode current (Ipa) and cathode current (Ipc) and the square root of the voltage in the CV test. (g) shows the b value calculated using the anode and cathode peaks in the CV test. (h) compares the capacitive contribution with and without the PEDOT:PSS layer according to the scan rate. (i) shows the Nyquist plots of the two EESDs, and the inset shows the equivalent circuit model. Figure 3 shows a comparative analysis of electrochromic and energy storage characteristics. (a) shows the light transmittance at various voltages of a polyviologen | zinc mesh electrochromic device (ECD) without a PEDOT:PSS layer. (b) shows the light transmittance at various voltages of a device containing a PEDOT:PSS layer. (c) shows photographs of the state of a polyviologen | zinc mesh electrochromic energy storage device (EESD) containing a PEDOT:PSS layer at -1.2 V, -0.6 V, and -0.2 V. (d) compares the switching time of the polyviologen | zinc mesh EESD with and without the PEDOT:PSS layer (-0.1 V and -2.0 V, at 40-second intervals). (e) shows the relationship between the change in optical density (ΔOD) and the charge density. (f) shows the results of comparing the long-term kinetic stability of the two EESDs with and without the PEDOT:PSS layer, measured at 40-second intervals at -0.1 V and -2.0 V. (g) shows the 0.5 mA cm⁻¹ of the polyviologen | zinc mesh EESD with and without the PEDOT:PSS layer. -2 This compares the discharge capacity at (h). (h) is for various current densities (0.1, 0.3, 0.5 mA cm⁻¹). -2 (i) shows the results of a comparison of discharge capacities measured in ). (i) is a radar plot comparing the performance of the polyviologen | zinc mesh EESD of the present invention with that of a conventional zinc-based electrochromic energy storage device. Figure 4 shows the electrochromic characteristics of a polyviologen | zinc mesh | WO3·2H2O electrochromic energy storage device (EESD). (a) schematically illustrates the structure and operating principle of the polyviologen | zinc mesh | WO3·2H2O EESD. (b) shows the light transmittance curves according to the transparent mode, visible light colored mode, NIR colored mode, and full colored mode in the wavelength range of 320–2500 nm, with the standard solar spectrum (AM 1.5 G) displayed in the background. (c) shows a photograph of the actual device in each mode, and the device size is 2.5 × 2.5 cm². (d) compares the combined solar radiation transmittance (T′) of the device measured in the visible light (380–2500 nm) and total solar radiation (380–2500 nm) spectra in four states. (e) shows the color and decolorization response times of the device at 600 nm (visible light) and 1800 nm (NIR), with the measurement voltages set to -0.1 V and -2.0 V and the time interval set to 20 seconds. (f) shows the relationship between the change in optical density (ΔOD) and charge density at 600 nm and 1800 nm. Figure 5 shows the energy consumption, energy recovery, and self-operating functions of a polyviologen | zinc mesh | WO₃·2H₂O electrochromic energy storage device. (a) shows a potentiostatic charge of 0.3 mA cm⁻¹ performed at -2.0 V for 60 seconds on a polyviologen | zinc mesh device. -2(b) shows the galvanostatic discharge at 0 V, the additional constant voltage discharge process performed for 60 seconds, and the change in light transmittance measured at 600 nm during this process. (b) shows the results of performing the same charge and discharge process on a WO3·2H2O | zinc mesh device and the change in light transmittance at 1800 nm. (c) shows an experimental photograph of driving an LED light by connecting two polyviologen | zinc mesh circuits (top) and two WO3·2H2O | zinc mesh circuits (bottom) in series. (d) shows an experimental photograph demonstrating self-coloring and self-bleaching functions implemented by connecting and disconnecting the electrodes of the polyviologen | zinc mesh circuit (top) and the WO3·2H2O | zinc mesh circuit (bottom). Specific details for implementing the invention

[0049] Hereinafter, an injection molded part breakage removal device according to an embodiment of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions to ensure clarity of the present invention.

[0050] Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.

[0051] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0052] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.

[0054] Materials

[0055] ITO-PET with a sheet resistance of 10 Ω / □ was provided by Wooyang GMS (Korea). Stainless steel mesh with a wire diameter of 50 mesh and 0.0012″ (inch) was purchased from TWP Inc., and electroplated zinc mesh electrodes were fabricated using this according to previously reported methods. PEDOT:PSS (1.3 wt% aqueous dispersion, Clevios pH 1000) was purchased from Heraeus.

[0056] The polyviologen used in the present invention is characterized by having the following polymer structure and exhibiting strong coloration in the visible light region through a unit electron pathway during the reduction process.

[0057]

[0058] WO3·2H2O was synthesized based on related research. In addition, all chemical reagents and solvents used in the experiment were purchased from TCI, Alfa Aesar, and Sigma Aldrich (Korea) and used as is without separate purification.

[0059] Polyviologen, PEDOT:PSS, and WO 3 ·2H 2 O Film production

[0060] First, the ITO-PET substrate was washed in an ultrasonic cleaner with deionized water, acetone, and isopropyl alcohol for 20 minutes each, and then dried with nitrogen purge (N₂ purge). Afterward, ultraviolet ozone (UVO) treatment was performed for 30 minutes to form a hydrophilic surface.

[0061] ITO-PET / polyviologen film production: Dissolve polyviologen in acetone and 10 g L -1 After preparing a solution of a certain concentration, it was uniformly coated onto an ITO-PET substrate using a spray gun on a hot plate heated to 80°C. Subsequently, a polyviologen film with a thickness of 6.5 μm was formed by heating and drying for an additional 30 minutes.

[0062] ITO-PET / Polyviologen / PEDOT:PSS Film Production: A 1.6 μm thick PEDOT:PSS layer was additionally coated on an ITO-PET / polyviologen substrate using a spray coating method. The preparation of the PEDOT:PSS solution and the spray coating method followed the methods reported in previous studies.

[0063] ITO-PET / WO 3 ·2H 2 O Film production : The WO3·2H2O layer was formed to a thickness of 2.6 μm using a previously reported method.

[0064] Manufacture of electrolytes and electrolyte-coated zinc mesh

[0065] Preparation of UV-curing hydrogel electrolytes : 1 M 2-acrylamido-2-methylpropanesulfonic acid (AMPS) was dissolved in deionized water as a negatively charged monomer, 1 M acrylamide (AAm) as a neutral monomer, 2 M zinc chloride (ZnCl2) as a salt source, 0.05 mol% N,N'-methylenebisacrylamide (MBAA) as a crosslinking agent, and 0.1 mol% 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone as a UV initiator. A UV-curing hydrogel electrolyte was prepared by stirring the mixture sufficiently until a completely transparent solution was obtained.

[0066] Manufacture of electrolytically coated zinc mesh A zinc mesh was fixed to glass using adhesive tape, with a gap of 180 μm at both the top and bottom. Subsequently, the prepared UV-curing electrolyte was applied, the glass was covered, and UV curing was performed for 3 minutes. After curing was complete, the glass and adhesive tape were removed to obtain a solid zinc mesh coated with the electrolyte (zinc mesh thickness: 36 μm, electrolyte layer thickness (sum of both sides): 180 + 180 = 360 μm, total thickness: 396 μm).

[0067] Manufacturing of electrochromic devices

[0068] The fabricated electrodes were placed directly on the top and bottom of a zinc mesh pre-coated with an electrolyte. Afterward, the electrodes were fixed by gently pressing them with glass, and the edges of the device were sealed using AB epoxy resin.

[0069] Electrochromic Energy Storage Smart Window Concept and Operation Mode

[0070] The present invention proposes an electrochromic energy storage smart window (EESD) capable of implementing four modes (transparent, visible light colored, near-infrared (NIR) colored, and fully colored), and is designed to operate adaptively according to time of day, season, and local climate conditions.

[0071] As shown in FIG. 1, the smart window of the present invention has a polyviologen | zinc mesh (Zn mesh) | WO3·2H2O structure and is based on a nearly symmetrical design. Polyviologen / PEDOT:PSS and WO3·2H2O are applied as cathodes to the top and bottom, respectively, and are attached to an ITO-PET substrate. Through this, transmittance can be controlled independently in the visible light and NIR regions.

[0072] The central layer consists of a zinc mesh coated with a UV-cured solid-state aqueous electrolyte, which serves as the anode. This structure is designed to enable independent self-charging (bleaching) and discharging (coloration) in the visible light and NIR regions.

[0073] Generally, when sunlight enters a building, visible light provides illumination while simultaneously generating heat, whereas NIR increases heat without visual effects. Therefore, the smart window of the present invention is designed to optimize indoor illumination and temperature control by individually adjusting these two spectral bands.

[0074] Cold weather (Fig. 1a)The WO3·2H2O layer remains transparent in a neutral state, allowing it to transmit NIR and heat the room. The polyviologen layer can maintain a transparent state to maximize indoor brightness and warmth, or switch to a colored mode to perform a privacy protection function. In other words, it can function as a dynamic blind.

[0075] Hot weather (Fig. 1b) The WO3·2H2O layer is colored to block NIR, thereby reducing heat inflow. The polyviologen layer can be adjusted according to indoor brightness and temperature requirements. For example, during times of strong sunlight, such as noon, the polyviologen layer is colored to block visible light and heat simultaneously, maintaining a comfortable indoor environment. Conversely, on cloudy days, at dawn, or at sunset, it remains transparent to maximize the use of natural light. In this way, the smart window of the present invention can effectively reduce dependence on artificial lighting and HVAC systems by dynamically adjusting solar transmittance, thereby significantly reducing the building's energy consumption.

[0076] Dual cathode and electrochemical performance analysis

[0077] In this invention, a polyviologen | zinc mesh (Zn mesh)-based EESD is proposed for the first time, thereby realizing four electrochromic modes utilizing a dual cathode structure. To achieve this, a polyviologen with high transparency was designed and synthesized, and the spray-coated polyviologen thin film exhibits a light transmittance of over 90% on an ITO-PET substrate, which demonstrates superior transparency compared to existing electrochromic materials. However, polyviologen has problems such as slow response speed due to low conductivity and reduced stability due to swelling. To solve these problems, PEDOT:PSS was introduced as a protective layer and a conductivity enhancement layer.

[0078] The overall structure of the device is shown in Fig. 2a, and Fig. 2b shows the shape and thickness of each layer. The thickness of the polyviologen layer was measured to be 6.5 μm, and the thickness of the PEDOT:PSS layer was measured to be 1.6 μm. The zinc mesh (Zn mesh, wire diameter 36 μm) maintains a high light transmittance of 88.5% on average and exhibits excellent transparency even after being coated with a UV-cured solid electrolyte. However, due to the absorption characteristics of moisture in the electrolyte, fine light absorption characteristics were observed at 1437 nm, 1930 nm, and 2500 nm. PEDOT:PSS has high electrical conductivity, excellent stability, and a low redox potential, and in particular, has the advantage of being able to lower interfacial resistance with an aqueous zinc ion electrolyte.

[0079] Electrochemical Reactions and Operating Principles

[0080] The electrochromic energy storage device (EESD) of the present invention has a structure in which reversible zinc deposition and dissolution occur at the zinc mesh anode during the charging and discharging process, and redox reactions proceed at the PEDOT:PSS and polyviologen cathodes. During charging, Zn ions (Zn²⁻) at the anode are reduced to metallic zinc (Zn) and deposited on the electrode surface, while PEDOT:PSS and polyviologen are oxidized at the cathode. Conversely, during discharging, Zn is reduced back to Zn 2+ It dissolves, and a reduction reaction between polyviologen and PEDOT:PSS occurs at the cathode. This reaction can be represented by the following electrochemical formula.

[0081] Anode reaction: Zn ↔ Zn 2+ + 2e -

[0082] Cathode reactions

[0083] PEDOT + (Transparent) + e - ↔ PEDOT (light blue)

[0084] PV 2+ (Transparent) + e - ↔ PV?? (Deep blue-violet)

[0085] Figure 2c illustrates the change in chemical structure during the redox reaction of polyviologen, which suggests that the electrochromic properties change reversibly during the charging and discharging process.

[0086] The EESD of the present invention utilizes such redox reactions to provide a function that stores electrical energy and discharges it when needed, thereby maximizing the energy efficiency of the smart window.

[0087] Electrochemical performance analysis

[0088] Cyclic Voltammetry (CV) analysis was performed to evaluate the electrochemical performance of the electrochromic energy storage device of the present invention, and the results are shown in Fig. 2d. In the device without the PEDOT:PSS layer, a single redox pair was observed, and a reduction peak at -0.66 V and an oxidation peak at -0.41 V were identified. This is PV 2+ PV + It was reduced to * and then back to PV 2+ This reflects the oxidation process. On the other hand, in devices containing a PEDOT:PSS layer, additional oxidation (-0.88 V) and reduction (-1.05 V) peaks were observed, which means that the redox reaction of PEDOT:PSS was added.

[0089] As shown in Fig. 2e, when the voltage decreases from -1.2 V to -1.05 V, PEDOT + It can be confirmed that the reduction reaction of polyviologen proceeds more rapidly at -0.58 V due to the ion conductivity enhancement effect of the PEDOT:PSS layer as it is converted to PEDOT. In addition, a significant increase in peak current was observed in the case of the device containing the PEDOT:PSS layer.

[0090] In Figure 2f, CV measurements were performed while varying the scan rate in the range of 1 to 10 mV / s. As a result, the anode (Ipa) and cathode (Ipc) peak currents showed a tendency to increase in proportion to the square root of the scan rate, but did not exhibit a linear correlation. This implies that the device is not simply a diffusion-controlled device, but is also influenced by surface capacitance.

[0091] In Fig. 2g, a log(i) versus log(v) plot was generated using the relationship i = av^b, and the value of b was calculated to be approximately 0.85. This indicates that the value of b is located between 0.5 (diffusion-dominated) and 1.0 (surface capacitance-dominated), confirming that charging of the device is controlled by a combination of diffusion and surface capacitance regardless of the presence or absence of the PEDOT:PSS layer. According to the analysis in Fig. 2h, it was confirmed that the capacitive contribution increased from 65.5% to 85.7% as the scan speed increased, and the presence or absence of the PEDOT:PSS layer did not have a significant effect on this.

[0092] This means that the electrochromic energy storage device of the present invention has a high surface capacity contribution and excellent surface-controlled charge storage, thereby possessing characteristics that enable high-speed charging and discharging.

[0093] Electrochemical Impedance Spectroscopy (EIS) and Interfacial Resistance Evaluation

[0094] In Figure 2i, the impedance of the device was measured using electrochemical impedance spectroscopy (EIS), and quantitative analysis was performed using an equivalent circuit model. As a result of the measurement, the intersection point with the real axis represents the internal resistance (Rs), and the diameter of the semicircle represents the interfacial charge transfer resistance (Rct). For the device without the PEDOT:PSS layer, the interfacial charge transfer resistance was measured to be 1356.7 Ω, but it decreased to 532.3 Ω when the PEDOT:PSS layer was applied. This result demonstrates that the PEDOT:PSS layer plays an important role in improving the electron transfer rate and optimizing the interfacial resistance.

[0095] Enhancement effect of electrochromic performance and energy storage performance of PEDOT:PSS layer

[0096] In the electrochromic energy storage device (EESD) of the present invention, the PEDOT:PSS layer enhances electrochemical performance and, consequently, provides the effect of significantly improving electrochromic characteristics. The PEDOT:PSS layer does not affect light transmittance in the transparent state, and the transmittance measured at various voltages from -1.5 V to -0.1 V was found to remain at approximately 79% (Figs. 3a and 3b). However, in the colored state, the device containing the PEDOT:PSS layer exhibited a transmittance of 73.5%, whereas the device without the PEDOT:PSS layer showed a transmittance of 35.5%, indicating a significant difference. Fig. 3c shows actual photographs of a polyviologen | zinc mesh EESD containing the PEDOT:PSS layer during the discharge (coloring) and charge (decolorization) processes. Furthermore, a distinct difference in response speed was confirmed depending on whether the PEDOT:PSS layer was applied (Fig. 3d). In the absence of the PEDOT:PSS layer, the coloring and decolorization times were measured to be 30.7 s and 37.9 s, respectively. When the PEDOT:PSS layer was applied, the coloring time was significantly reduced to 1.8 s and the decolorization time to 0.8 s due to improved ion mobility and electron transfer. This marks the first instance of a viologen-based electrochromic device achieving a response speed of less than 1 second, demonstrating performance that surpasses most existing electrochromic materials. The device with the PEDOT:PSS layer maintains a deeper coloring state, resulting in increased optical density and a coloring efficiency (CE) of 133.47 C cm⁻¹. -2 At 362.24 cm -2 It was improved (Fig. 3e).

[0097] Protective effect and long-term stability of the PEDOT:PSS layer

[0098] The PEDOT:PSS layer serves to protect the polyviologen layer and effectively prevents swelling and ionic corrosion of the polyviologen by blocking direct contact with moisture and zinc ions in the electrolyte. This protective effect was confirmed through a long-term cycling stability test (Fig. 3f). The device containing the PEDOT:PSS layer maintained 80.7% of the initial change in transmittance (ΔT) even after 4,800 seconds of cycling operation. In contrast, without the PEDOT:PSS layer, only 35.5% of ΔT was maintained, and relatively rapid performance degradation was observed.

[0099] Effect of enhancing energy storage performance of PEDOT:PSS layer

[0100] The PEDOT:PSS layer plays a role in dramatically enhancing the energy storage capacity of viologen-based EESDs by inducing polyviologen molecules to participate more actively in the redox reaction. As shown in the discharge test results illustrated in Fig. 3g, 0.5 mA cm⁻¹ is obtained when the PEDOT:PSS layer is not included. -2 At 73.2 mAh m -2 While it showed a discharge capacity of, 141.9 mAh m⁻¹ when the PEDOT:PSS layer was applied. -2The capacity increased by nearly twofold. In addition, similar performance improvements were confirmed in capacity measurements at various current densities. Figure 3h shows the results of a comprehensive comparison between the device of the present invention and a conventional zinc-based EESD as a radar chart, and the polyviologen | zinc mesh EESD containing a PEDOT:PSS layer exhibited superior performance compared to the conventional device, particularly in response speed and coloration efficiency. As such, by introducing a PEDOT:PSS layer, the electrochromic energy storage device of the present invention can provide improved response speed, high coloration efficiency, excellent long-term stability, and increased energy storage performance, thereby maximizing practicality as a large-area smart window and a next-generation electrochromic device.

[0101] Multimode Implementation and Optical Properties of Electrochromic Energy Storage Devices Based on Dual Cathode Structure

[0102] Unlike conventional zinc foils, the electrochromic energy storage device (EESD) of the present invention has the advantage of being able to form a uniform electric field by applying a zinc mesh as the anode, which allows operation on both sides while maintaining transparency. Through this, a large-area device with electrochromic cathodes placed on each side can be realized, and a new structure was designed in which a zinc mesh anode is located at the center. Based on this structure, four electrochromic modes capable of independently controlling visible light and NIR were realized by utilizing the excellent near-infrared (NIR) transmittance control characteristics of WO3·2H2O (Fig. 4a). That is, by applying the coloring of WO3·2H2O to NIR control and the coloring of polyviologen to visible light control, four smart window operation modes—transparent mode, visible light colored mode, NIR colored mode, and fully colored mode—were realized. Fig. 4b shows the transmittance spectra for each of the four modes in the range of 320 to 2500 nm. In transparent mode, it exhibits high transmittance in the visible light and NIR bands from 380 to 2500 nm. In visible light colored mode, it maintains high transmittance from 380 to 2500 nm. The NIR colored mode exhibits a transmittance pattern opposite to that of the above, and in full colored mode, it exhibits low transmittance across the entire range from 320 to 2500 nm. Additionally, in all modes, the transmittance in the ultraviolet (UV) region (320 to 380 nm) is low, providing a UV blocking effect and enabling it to perform a human body protection function. Figure 4c shows actual photographs of the four modes, and the device size is 2.5 × 2.5 cm².

[0103] Optical transmittance and sunlight control performance

[0104] For the polyviologen | zinc mesh | WO₃·2H₂O EESD of the present invention, the total light transmittance (T) and solar radiation intensity-weighted transmittance (T′) in visible light (380-780 nm), NIR (780-2500 nm), and the entire solar spectrum (380-2500 nm) were calculated, and the results are presented in Fig. 4d. The visible light coloring mode and the NIR coloring mode perform the function of selectively controlling the transmission or blocking of solar and radiant energy in their respective spectral bands. The transparent mode and the fully colored mode perform the function of controlling solar radiation across the entire spectral band, and it was confirmed that overall light transmission control is possible by exhibiting solar transmittances of 71.32% and 4.15%, respectively.

[0105] Analysis of response speed and coloring efficiency

[0106] The response speed of the polyviologen | zinc mesh | WO3·2H2O EESD of the present invention transitioning from a transparent mode to a fully colored mode was evaluated at 600 nm (visible light) and 1800 nm (NIR) (Fig. 4e). The switching at 600 nm reflects the behavior of the polyviologen-based EESD, while the switching at 1800 nm reflects the behavior of the WO3·2H2O-based EESD. The measurement results showed an ultrafast response at 600 nm, with a bleaching speed of 0.8 s and a coloring speed of 2.0 s. At 1800 nm, the coloring and bleaching times were 3.6 s and 2.1 s, respectively, confirming that it provides superior performance compared to most existing tungsten oxide-based devices. Furthermore, the coloration efficiency (CE) measured at 600 nm and 1800 nm was 272.63 C cm⁻¹, respectively. -2 and 211.58 C cm -2It was found that the coloring method based on a dual cathode structure increases charge density, thereby causing a change in the CE value; however, it was confirmed that the CE value of this device maintains a competitive level compared to existing studies. The electrochromic energy storage device of the present invention provides the ability to independently control visible light and NIR according to various environments, and can provide higher performance compared to existing smart windows and energy storage devices through ultra-fast response speed and improved coloring efficiency.

[0107] Energy Consumption and Energy Recovery Efficiency Analysis

[0108] One of the key indicators for evaluating the performance of electrochromic energy storage devices (EESDs) is energy consumption and energy return efficiency, which play a crucial role in energy conservation and carbon emission reduction. The energy return efficiency was evaluated by analyzing the energy consumed and recoverable during the charging and discharging processes of the polyviologen | zinc mesh and WO3·2H2O | zinc mesh-based devices of the present invention.

[0109] As shown in Fig. 5a, the fully discharged polyviologen | zinc mesh element underwent a potentiostatic charging process at -2.0 V for 60 seconds, during which a total of 132.50 mWh m⁻² -2 0.3 mA cm of energy was consumed. Afterwards, 0.3 mA cm -2 As a result of performing galvanostatic discharge at a current density, a total of 53.01 mWh m -2 Energy was released. Finally, the final coloring process was completed by performing an additional potentiostatic discharge at 0 V for 60 seconds, and the energy consumed in this process was 0.0018 mWh m -2It was at a negligible level. Overall, a total of 132.5018 mWh m per charge / discharge cycle. -2 Energy was consumed, and the energy recovered during discharge was 53.01 mWh m -2 As a result, the energy recovery efficiency of the polyviologen | zinc mesh-based device of the present invention was calculated to be 40.0%. Similarly, the energy recovery efficiency of the WO3·2H2O | zinc mesh-based device was evaluated and found to be 30.9%. The recovered energy can be used to power electronic devices such as lighting and heating, ventilation, and air conditioning (HVAC) systems. In addition, the polyviologen | zinc mesh and WO3·2H2O | zinc mesh-based circuits of the present invention generate open-circuit voltages (OCV) of 1.23 V and 1.05 V, respectively, and it was confirmed that connecting two identical devices in series can provide an open-circuit voltage of 2 V or more, thereby supplying sufficient power to drive LED lighting (1.8 V, 2.2 W).

Claims

Claim 1 An oxidation electrode used in an electrochromic energy storage device, comprising: a metal mesh electrode; and a curable solid electrolyte layer formed on the surface of the mesh electrode, wherein the solid electrolyte layer has a polymer main chain comprising an acrylic monomer and a polymer side chain comprising an anionic functional group, and forms a cross-linked polymer network cross-linked by methylene (-CH2-) cross-linking, wherein a cation is dispersed within the cross-linked solid electrolyte, and the cation is zinc, magnesium, calcium, or a combination thereof. Claim 2 An oxidation electrode used in an electrochromic energy storage device, comprising: a metal mesh electrode; and a curable solid electrolyte layer formed on the surface of the mesh electrode, wherein the solid electrolyte layer has a polymer main chain comprising an acrylic monomer and a polymer side chain comprising an anionic functional group, forms a cross-linked polymer network cross-linked by methylene (-CH2-) cross-linking, wherein a cation is dispersed within the cross-linked solid electrolyte, and the anion is a sulfate ion. Claim 3 An oxidation electrode used in an electrochromic energy storage device, wherein, in claim 1 or 2, the acrylic monomer is acrylamide (AAm), methacrylamide (MAAm), hydroxyethyl acrylamide (HEAAm), or a combination thereof. Claim 4 delete Claim 5 delete Claim 6 Metal mesh electrode; The apparatus comprises a curable solid electrolyte layer formed on the surface of the mesh electrode, wherein the solid electrolyte layer has a polymer main chain containing an acrylic monomer and a polymer side chain containing an anionic functional group, forms a cross-linked polymer network cross-linked by methylene (-CH2-) cross-linking, and cations are dispersed within the cross-linked solid electrolyte, and the solid electrolyte is prepared by a method of preparing a polymer solution by dissolving an acrylic monomer, a monomer containing an anionic functional group, a crosslinking agent, a metal salt, and a UV initiator in deionized water, applying the prepared polymer solution to the mesh electrode, and then curing it by irradiating with UV light, wherein the acrylic monomer is acrylamide (AAm), methacrylamide (MAAm), hydroxyethyl acrylamide (HEAAm), or a combination thereof, and the monomer containing an anionic functional group is 2-acrylamido-2-methylpropanesulfonic acid (AMPS), sodium 4-styrenesulfonic acid (SSS), acrylic acid (AA), An oxide electrode used in an electrochromic energy storage device, which is methacrylic acid (MAA) or a combination thereof. Claim 7 delete Claim 8 delete Claim 9 An oxidation electrode used in an electrochromic energy storage device, wherein the crosslinking agent is N,N'-methylenebisacrylamide (MBAA), polyethylene glycol diacrylate (PEGDA), divinylbenzene (DVB), or a combination thereof. Claim 10 An oxidation electrode used in an electrochromic energy storage device, wherein the metal salt is zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc nitrate (Zn(NO3)2), magnesium chloride (MgCl2), calcium chloride (CaCl2), or a combination thereof. Claim 11 In claim 10, the UV initiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, Irgacure 2959, Irgacure 184, Darocur 1173, or a combination thereof, an oxide electrode used in an electrochromic energy storage device. Claim 12 delete Claim 13 A smart window having transparent large-area electrochromic and energy storage functions, comprising: a metal mesh electrode; an oxidation electrode including a curable solid electrolyte layer formed on the surface of the mesh electrode; a first reduction electrode portion located on one side of the oxidation electrode; and a first power supply unit connecting the oxidation electrode and the first reduction electrode portion, wherein the first reduction electrode portion includes a first electrochromic layer laminated on one side of the oxidation electrode; and a first transparent electrode laminated on the first electrochromic layer; a second reduction electrode portion located on the other side of the oxidation electrode; and a second power supply unit connecting the oxidation electrode and the second reduction electrode portion, wherein the second reduction electrode portion includes a second electrochromic layer laminated on the other side of the oxidation electrode; and a second transparent electrode laminated on the second electrochromic layer, wherein the transmission and blocking wavelength bands of the first electrochromic layer and the second electrochromic layer are different from each other. Claim 14 A smart window having transparent large-area electrochromic and energy storage functions, comprising: a metal mesh electrode; an oxidation electrode including a curable solid electrolyte layer formed on the surface of the mesh electrode; a first reduction electrode portion located on one side of the oxidation electrode; and a first power supply portion connecting the oxidation electrode and the first reduction electrode portion, wherein the first reduction electrode portion includes a first electrochromic layer laminated on one side of the oxidation electrode; and a first transparent electrode laminated on the first electrochromic layer, wherein the first electrochromic layer includes polyviologen, and further includes a PEDOT:PSS conductive polymer layer between the oxidation electrode and the first electrochromic layer. Claim 15 A transparent, large-area smart window having electrochromic and energy storage functions, wherein the first electrochromic layer comprises polyviologen, further comprises a PEDOT:PSS conductive polymer layer between the oxidation electrode and the first electrochromic layer, and the second electrochromic layer comprises WO3·H2O or WO3.

Citation Information

Patent Citations

  • Solid polymer electrolyte composition and electrochromic device using the same

    KR1020130013949A

  • Electrochromism element

    KR1020180082213A

  • Composition of polymer electrolyte, method for preparing polymer electrolyte and an electrochromic device comprising the same.

    KR1020190064044A